5th ICEG environmental geotechnics opportunities, challenges and responsibilities for environmental geotechnics : proceedings of the ISSMGE's fifth international congress organized by the Geoenvironmental Research Centre Cardiff University and held at Cardiff City Hall on 26-30th June 2006 - Thomas, H. R. (Thomas Telford, 2006)
This congress brings together practitioners, academics and the public sector to highlight the latest ideas and developments in environmental geotechnics and related fields. Consisting of 1658 pages with contributions from over 200 eminent authors from across the globe, this 2-volume set presents current thinking and practice.